Resin composition, method for producing resin composition, and structure
The resin composition achieves uniform dispersion of large-diameter conductive particles by using partially coated particles with a small particle size filler, addressing the issue of short-circuits in anisotropic conductive adhesives.
Patent Information
- Application Number
- JP2018033955
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-03-06
- Filing Date
- 2018-02-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2038-02-27
AI Technical Summary
Existing resin compositions struggle with the uniform dispersion of large-diameter conductive particles in anisotropic conductive adhesives, leading to potential short-circuits between electrode terminals of electronic components.
A resin composition is developed using partially coated particles, where a small particle size filler is used to coat part of the surface of large-diameter particles, improving their dispersibility in an insulating binder. The method involves stirring large-diameter particles with a small particle size filler to create first coated particles, and then mixing these particles with an insulating binder to achieve uniform dispersion.
The proposed solution allows for the uniform dispersion of large-diameter conductive particles, effectively suppressing short-circuits between electrode terminals and maintaining the quality stability of the resin composition.
Smart Images

Figure 0007666886000003 
Figure 0007666886000004 
Figure 0007666886000005
Abstract
Description
[Technical field]
[0001] The present technology relates to a resin composition, a method for producing a resin composition, and a structure. [Background technology]
[0002] In a resin composition containing particles, high dispersibility is required due to various factors such as a decrease in performance caused by aggregation of the particles (see, for example, Patent Document 1). This is particularly required in resin compositions for electronic components and adhesives for electronic components. This is because it is difficult to maintain the quality stability of the resin composition when the dispersibility of the particles is low.
[0003] One example of an adhesive for electronic components is a circuit connecting material, and the anisotropic conductive adhesive therein is generally one in which conductive particles are dispersed in an insulating binder (see, for example, Patent Documents 2 to 4). However, even if the conductive particles in the anisotropic conductive adhesive are dispersed immediately after production, they may aggregate. Aggregation of conductive particles can lead to a decrease in the conductive particle capture efficiency and short circuits between electrode terminals of electronic components. For this reason, an insulating coating is sometimes formed in advance on the surface of the conductive particles (see, for example, Patent Document 2).
[0004] However, forming an insulating coating on the surface of the conductive particles tends to increase the manufacturing cost. In particular, the larger the particle diameter of the conductive particles, the larger the surface area of the conductive particles becomes, and the more difficult it becomes to form an insulating coating on the surface of the conductive particles, which tends to increase the manufacturing cost. Therefore, even when the particle diameter of the conductive particles is large, it is required to uniformly disperse the conductive particles in a simple manner to suppress short circuits between electrode terminals of electronic components.
[0005] Even when the particle diameter of the particles dispersed in the insulating binder is small, it is required that the particles be dispersed uniformly. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-134887 A [Patent Document 2] JP 2015-133301 A [Patent Document 3] JP 2014-241281 A [Patent Document 4] Japanese Patent Application Publication No. 11-148063 Summary of the Invention [Problem to be solved by the invention]
[0007] In addition, the present technology has been proposed in consideration of such conventional circumstances, and provides a resin composition capable of uniformly dispersing particles by a simple method, a method for producing a resin composition, and a structure.
[0008] In addition, in the case of an anisotropic conductive adhesive, the present invention provides an anisotropic conductive adhesive that can uniformly disperse conductive particles in a simple manner even when the particle diameter of the conductive particles is large, and that can suppress short circuits between electrode terminals of electronic components, a method for manufacturing an anisotropic conductive adhesive, and a connection structure. [Means for solving the problem]
[0009] The resin composition according to the present technology uses small particle size fillers to suppress the formation of large particle size fillers. The surface Covered Coated large particles and a small particle size filler and an insulating binder. Coated large particles are dispersed, and the number average particle diameter of the large diameter particles is 2 μm or more. 20μm the number average particle diameter of the small particle diameter filler is 0.02% or more and 0.143% or less of the number average particle diameter of the large particle diameter particles and is 10 nm or more, and the amount of the small particle diameter filler relative to the large particle diameter is 11.6% by volume to 38.7% by volume It is.
[0010] The method for producing a resin composition according to the present invention is to produce a resin composition having a number average particle diameter of 2 μm or more. 20μmThe large particles are coated with the small particle filler by mixing the large particles having a number average particle diameter of 0.02% to 0.143% of the number average particle diameter of the large particles and 10 nm or more. First coated particle and a step (A) of obtaining A mixture of the first coated particles and the small particle size filler obtained in the step (A) By mixing the small particle filler with the insulating binder, the large particle filler is prevented from being filled with the insulating binder. The surface Covered Second coated particle and (B) obtaining a resin composition in which the small particle diameter filler is dispersed in the insulating binder. In the step (A), the amount of the small particle diameter filler relative to the large particle diameter filler is 11.6% by volume to 38.7% by volume The large particle and the small particle filler are mixed so that In the step (B), the amount of the small particle size filler relative to the large particle size is 38.7% by volume to 11.6% by volume. .
[0011] The anisotropic conductive adhesive of this technology uses insulating filler to separate conductive particles. The surface Covered Coated Conductive Particles and an insulating filler and an insulating binder, The coated conductive particles are dispersed, and the number average particle diameter of the conductive particles is 7 μm or more. 20μm the number average particle diameter of the insulating filler is 0.02 to 0.143% of the number average particle diameter of the conductive particles and is 10 nm or more, and the amount of the insulating filler relative to the conductive particles is 11.6% by volume to 38.7% by volume It is.
[0012] The method for producing an anisotropic conductive adhesive according to the present technology includes a step (A) of obtaining first coated conductive particles in which the conductive particles are coated with the insulating filler by stirring conductive particles having a number average particle diameter of 7 μm or more and 20 μm or less and an insulating filler having a number average particle diameter of 0.02 to 0.143% of the number average particle diameter of the conductive particles and 10 nm or more, and a step (B) of obtaining an anisotropic conductive adhesive in which second coated conductive particles in which the surfaces of the conductive particles are coated with the insulating filler are dispersed in the insulating binder by stirring the mixture of the first coated conductive particles and the insulating filler obtained in the step (A) and an insulating binder, and in the step (A), the conductive particles and the insulating filler are arranged so that the amount of the insulating filler relative to the conductive particles is 11.6 vol % to 38.7 vol %. Combined In the step (B), the amount of the insulating filler relative to the conductive particles is also 11.6 vol % to 38.7 vol %.
[0013] The connection structure according to the present technology comprises a first electronic component and a second electronic component connected via an anisotropic conductive film made of the above-mentioned anisotropic conductive adhesive. Effect of the Invention
[0014] According to the present technology, by forming partially coated particles in which a portion of the surface of a large particle is coated with a small particle size filler, the large particle can be uniformly dispersed.
[0015] According to the present technology, even if the particle diameter of the conductive particles is large, the conductive particles (coated conductive particles whose surface is partially coated with insulating filler) can be uniformly dispersed in a simple manner, thereby preventing short circuits between electrode terminals of electronic components. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a connection structure according to the present embodiment. [Diagram 2]FIG. 2 is a diagram showing an example of a mixture obtained by stirring conductive particles and insulating filler. [Diagram 3] FIG. 3 is a diagram showing an example of an anisotropic conductive adhesive obtained by mixing coated conductive particles coated with an insulating filler and an insulating binder. [Figure 4] FIG. 4 is a diagram showing conductive particles that are not coated with an insulating filler. [Diagram 5] FIG. 5 is a diagram showing an example of an anisotropic conductive adhesive obtained by mixing conductive particles not covered with an insulating filler with an insulating binder. [Figure 6] FIG. 6 is a diagram showing an example of a mixture obtained by stirring conductive particles and insulating filler. [Figure 7] FIG. 7 is a cross-sectional view that illustrates a first example of a partially coated particle to which the present technology is applied. [Figure 8] FIG. 8 is a cross-sectional view that illustrates a second example of a partially coated particle to which the present technology is applied. [Figure 9] FIG. 9 is a cross-sectional view that illustrates a third example of a partially coated particle to which the present technology is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] This technology improves the dispersibility of large particles in an insulating binder by forming partially coated particles in which a part of the surface of the large particle is coated with a small particle filler. On the other hand, when the entire surface of the large particle is coated with a small particle filler, the amount of the small particle filler relative to the large particle is too large, and the dispersibility of the large particle in the insulating binder tends to decrease.
[0018] The partially coated particles can be obtained by mixing powders of large particles and small particle fillers (preferably mixing only these), coating the surfaces of the large particles with the small particle fillers, and then mixing (kneading) this mixture with a resin composition to peel off some of the small particle fillers that cover the surfaces of the large particles. Paradoxically speaking, if partially coated particles are formed, the amount of small particle fillers relative to the large particles is appropriate, and it can be said that the dispersibility of the large particles in the insulating binder is high. This can be done, for example, by using a planetary stirring device or the like and applying a high shear (shear force), so that the coating of the small particle fillers on the surfaces of the large particles and partial peeling can be efficiently performed.
[0019] The first embodiment will be described below.
[0020] [First embodiment] <Resin composition> The resin composition according to the present embodiment contains partially coated particles in which a part of the surface of a large particle is coated with a small particle filler, a small particle filler, and an insulating binder, the partially coated particles are dispersed, the particle diameter of the large particle is 2 μm or more, the particle diameter of the small particle filler is 0.02 to 5.0% of the particle diameter of the large particle, and the amount of the small particle filler relative to the large particle is less than 156 volume %. Note that the expression 0.02 to 5.0% means 0.02% or more and 5.0% or less unless otherwise specified.
[0021] In this specification, the particle size of the large particle can be a value measured by an image type particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Instruments). The number is preferably 1000 or more, and more preferably 2000 or more. The particle size of the small particle filler can be, for example, observed under an electron microscope and taken as the average value of any 100 particles, and the accuracy can be improved by making it 200 particles or more.
[0022] The amount (volume %) of the small particle size filler relative to the large particle size can be calculated using the following formula. Amount (volume %) of small particle size filler (B) relative to large particle size (A) ={(Bw / Bd) / (Aw / Ad)}×100 Aw: Mass composition of large particles (A) (mass%) Bw: Mass composition of small particle size filler (B) (mass%) Ad: Specific gravity of large particles (A) Bd: Specific gravity of small particle size filler (B)
[0023] 7 to 9 are cross-sectional views each showing a first to third example of a partially coated particle to which the present technology is applied. As shown in FIG. 7 to FIG. 9, the partially coated particle 20 has a part of the surface of a large particle 21 coated with a small particle diameter filler. In other words, the partially coated particle 20 has a coated part 22 coated with a small particle diameter filler and an exposed part 23 in which the surface of the large particle is exposed. The partially coated particle 20 may have the exposed part 23 mottled on the whole surface as shown in FIG. 7, the exposed part 23 may be partially present as shown in FIG. 8, or the exposed part 23 may be more than half of the whole as shown in FIG. 9. This is because the first objective is to easily obtain the dispersibility of the partially coated large particle obtained by this method, and it is not because the performance of the large particle is obtained by the coating state.
[0024] The partially coated particles 20 may be confirmed to be partially coated in a planar observation using an electron microscope or the like after the resin composition is formed into a film. It is preferable that the same results are obtained by changing the observation location several times. For detailed confirmation, it is sufficient to confirm that at least a part of the outermost surface is coated in the cross section of the partially coated particles 20. It is possible to confirm more precisely and simply by observing the same location on the front and back sides of the film body to be observed. With this method, it is possible to determine whether or not the large diameter particles are partially coated. It is considered possible to determine the case where the peeled small particle diameter filler and the large diameter particles overlap by adjusting the focal length.
[0025] The proportion of the coating portion 22 in the partially coated particles 20 can also be confirmed by, for example, forming the above-mentioned resin composition into a film and then observing the surface of the film with an electron microscope or the like. Alternatively, the resin composition can be cured or frozen, and the outermost surfaces of the cross sections of 100 randomly selected partially coated particles can be observed with an electron microscope to determine the average value of the proportions of the coating portions of the 100 randomly selected partially coated particles. The average value of the proportions of the coating portions of such partially coated particles may be, for example, 15% or more and less than 100%, and may be 30 to 95%.
[0026] The proportion of the number of the partially coated particles 20 to the total of the fully coated particles and the partially coated particles is 70% or more, preferably 80% or more, and more preferably 95% or more. The proportion of the number of the partially coated particles 20 can be determined, for example, by curing or freezing the resin composition, observing any 100 fully coated particles and partially coated particles with an electron microscope, and counting the number of the partially coated particles to any 100 fully coated particles and partially coated particles.
[0027] The large-diameter particles are not particularly limited, and the material is appropriately selected according to the function of the resin composition. For example, when the resin composition is given electrical conductivity, conductive particles, metal particles, etc. are selected, and when the resin composition is given a spacer function, acrylic rubber, styrene rubber, styrene olefin rubber, silicone rubber, etc. are selected. This is not particularly limited as long as it can be coated or partially coated in combination with a small particle size filler, and may be an organic material, an inorganic material, or a combination of an organic material and an inorganic material such as metal-plated resin particles. One type may be used alone, or two or more types may be used in combination. If one type is used alone, the evaluation of dispersibility is easy. If two or more types are used, it is preferable that the appearance is clearly different for the same reason.
[0028] The particle diameter of the large diameter particles is 2 μm or more. Although there is no particular upper limit to the particle diameter of the large diameter particles, for example, when the large diameter particles are conductive particles, from the viewpoint of the capture efficiency of the conductive particles in the connection structure, the particle diameter is preferably, for example, 50 μm or less, and more preferably 20 μm or less.
[0029] The solid density of the large particles in the resin composition can be adjusted appropriately depending on the purpose, but the lower limit is 20 particles / mm 2 It is preferable that the number of particles is 100 or more per mm. 2 More preferably, it is 150 pieces / mm 2 It is even more preferable that the number is equal to or more than 80,000 particles / mm. If the number is too small, the margin for adjusting the ratio with the small particle size filler is small, making reproducibility difficult. The upper limit is 80,000 particles / mm. 2 It is preferable that the number of pieces is 70,000 pieces / mm or less. 2 More preferably, it is 65,000 pieces / mm or less. 2 It is even more preferable that the number density is less than 1.3 times the large particle diameter. If the number density of the large particle becomes too large, it becomes difficult to cover the small particle diameter filler or mix it with the resin composition. The number density can be obtained by forming a film on the smooth surface of the support and observing it in the plane view. The thickness in this case can be 1.3 times or more the large particle diameter or 10 μm or more, and the upper limit can be 4 times or less the large particle diameter, preferably 2 times or less, 40 μm or less. Since this thickness is derived from the resin composition, it is difficult to determine it uniquely, so the range is set in this way. For the plane view observation, a metal microscope or an electron microscope such as SEM can be used. It may be obtained by measuring individual large particle diameters from the observation image, or it may be measured using a known image analysis software (WinROOF (Mitani Shoji Co., Ltd.) is an example). In the case of a resin composition, it varies depending on the thickness when made into a film, so it can be determined by the plane view number density of 1.3 times or 4 times the thickness of the large particle. In addition, when a solvent is contained, it is the thickness after drying.
[0030] The small particle size filler is mostly dispersed in the insulating binder, and a part of it covers a part of the surface of the large particle. An insulating filler can be used as the small particle size filler. Examples of the insulating filler include oxides such as titanium oxide, aluminum oxide, silica, calcium oxide, and magnesium oxide, hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, magnesium carbonate, zinc carbonate, and barium carbonate, sulfates such as calcium sulfate and barium sulfate, silicates such as calcium silicate, and nitrides such as aluminum nitride, boron nitride, and silicon nitride. The insulating filler may be used alone or in combination of two or more types.
[0031] The upper limit of the particle size of the small particle filler can be 14% or less, preferably 0.3% or less, of the large particle. Alternatively, it is preferably 100 nm or less, and more preferably 50 nm or less. By making the small particle filler not too large relative to the surface area of the large particle, defects such as scratches on the surface of the large particle can be suppressed. In addition, the lower limit of the particle size of the small particle filler is preferably 10 nm or more. By making the small particle filler not too small relative to the surface area of the large particle, aggregation of the large particle can be more effectively suppressed. If it is too small, the viscosity of the resin composition increases too much, which may affect dispersibility.
[0032] Due to the size relationship between the large particles and the small particle filler described above, the ratio of particle sizes between the large particles and the small particle filler (particle size of the small particle filler / particle size of the large particles) is 0.02 to 5.0%, and preferably 0.02 to 2.5%.
[0033] In addition, the volume ratio of the small particle diameter filler to the large particle diameter filling material that satisfies the above-mentioned particle diameter ratio is less than 156% by volume. If it exceeds this, it becomes difficult to easily obtain uniform dispersion in the resin. The lower limit value is naturally greater than 0%, but it is difficult to determine it uniquely because the shape of the filler is also involved in addition to the ratio of the size of the large particle diameter filler to the small particle diameter filler. However, it is considered that there is no particular problem if it is 0.78% or more, and it is preferably 3.9% or more, and more preferably 7.8% or more. The upper limit value is preferably 78% by volume or less, and more preferably 39% or less. These values can be appropriately selected based on the relationship between the large particle diameter filler and the small particle diameter filler. By satisfying such conditions, the dispersibility of the large particle diameter can be improved.
[0034] The insulating binder (insulating resin) may be a known insulating binder. Examples of the curing type include a heat curing type, a photocuring type, and a photothermal combined curing type. Examples include a photoradical polymerization type resin containing a (meth)acrylate compound and a photoradical polymerization initiator, a thermal radical polymerization type resin containing a (meth)acrylate compound and a thermal radical polymerization initiator, a thermal cationic polymerization type resin containing an epoxy compound and a thermal cationic polymerization initiator, and a thermal anionic polymerization type resin containing an epoxy compound and a thermal anionic polymerization initiator. Also, a known pressure-sensitive adhesive composition may be used.
[0035] The resin composition may further contain other components other than the partially coated particles, the small particle size filler, and the insulating binder, as necessary, such as a solvent (methyl ethyl ketone, toluene, propylene glycol monomethyl ether acetate, etc.), a stress relaxation agent, a silane coupling agent, etc.
[0036] As described above, the resin composition has high dispersibility because the particle diameter of the large particles is 2 μm or more, the particle diameter of the small particle filler is 0.02 to 5.0% of the particle diameter of the large particles, and the amount of the small particle filler relative to the large particles is less than 156 volume %.
[0037] In addition, for example, when the resin composition functions as a spacer between a first member and a second member, the amount of small particle size filler adhering to the large particle size is small, so that the spacer can have a diameter approximately equal to that of the large particle size. In addition, for example, when the resin composition is used as an anisotropic conductive adhesive in which the large particle size is a conductive particle and the small particle size filler is an insulating filler, the amount of insulating filler adhering to the conductive particle is small, so that excellent conductivity can be obtained.
[0038] In addition, for example, when the resin composition is made into an anisotropic conductive film made of an anisotropic conductive adhesive in which the large particles are conductive particles and the small particle size filler is an insulating filler, the conductive particles have a very high dispersibility, so that the number density of the conductive particles in the entire anisotropic conductive film (number / mm 2 ) and the number density (number / mm2) of conductive particles in a 0.2 mm x 0.2 mm area arbitrarily extracted from the anisotropic conductive film. 2 ) can be 15% or less. Here, the difference in number density is the difference between the maximum value and the minimum value of the number density of the conductive particles in an arbitrarily extracted predetermined region.
[0039] <Method of producing resin composition> The method for producing a resin composition according to the present embodiment includes the following steps (A) and (B).
[0040] [Process (A)] In step (A), the large particles and the small particle size filler having a particle size smaller than that of the large particles are stirred to obtain the first coated particles. In step (A), the large particles are coated with the small particle size filler in order to suppress the aggregation of the second coated particles obtained in step (B). In addition, in step (A), as described above, the large particles and the small particle size filler are blended so that the amount of the small particle size filler relative to the large particles is less than 156 volume %. By satisfying such conditions, the coating of the small particle size filler on the surface of the large particles can be easily progressed in step (A), and the small particle size filler in the first coated particles can be easily separated in step (B).
[0041] The method of mixing the large particles and the small particle filler may be either a dry method or a wet method, and the dry method is preferred. This is because the method used in known toners and the like can be applied. Examples of devices for mixing the large particles and the small particle filler include planetary mixing devices, shakers, lab mixers, mixing propellers, and the like. In particular, from the viewpoint of covering the large particles with a relatively large average particle size with the insulating filler, a planetary mixing device with a high shear is preferred. Methods using media such as ball mills and bead mills are not excluded, but are not preferred. This is because if there are other things to be removed besides the large particles and the small particle filler, it is undesirable in terms of productivity. In addition, when such media (balls or beads) are used, the number of factors to consider the influence on the surface state of the large particles and the small particle filler increases, making product design difficult. A planetary mixing device is a mixing device that rotates and revolves a container containing a material (a mixture of large particles and small particle filler). The batch method of producing each container is also preferable in that quality control is easier, and it is easy to obtain a resin composition in which large-diameter particles and small-diameter fillers are dispersed with high precision.
[0042] The preferred ranges of the large and small particle size fillers are the same as those of the large and small particle size fillers described above in the anisotropic conductive adhesive. In particular, from the viewpoint of covering the large particles with the small particle size filler in step (A), it is preferable to use the large particles in a dry powder state.
[0043] [Process (B)] In step (B), the first coated particles and the insulating binder are stirred to obtain a resin composition in which the second coated particles and small particle size filler particles that have separated from the large particle size particles in the first coated particles are dispersed in the insulating binder.
[0044] In step (B), the first coated particles are stirred in the insulating binder, and friction and high shear between the small particle diameter filler in the first coated particles and the large particle diameter filler are applied, so that the small particle diameter filler is separated from the large particle, and a part of the surface of the large particle is coated with the small particle diameter filler to obtain a partially coated particle (second coated particle). In addition, the small particle diameter filler separated from the large particle in the first coated particle is interposed between the second coated particles, so that the aggregation of the second coated particles can be suppressed. In this way, by performing step (B), the aggregation of the second coated particles can be suppressed, and the second coated particles can be dispersed in the insulating binder. At this time, the small particle diameter filler is also dispersed at the same time. That is, in the present invention, the number of mixing steps is minimized. For example, it is possible to add a small particle diameter filler each time to adjust the viscosity as in the conventional method, but it is easy to predict that it will be difficult to obtain a reproducible dispersion state. However, by adjusting the powder (large particle and small particle filler) in advance and mixing the resin composition with it, the required amount can be adjusted, which is desirable in terms of material costs and manufacturing costs. In addition, since it is easy to compare batches with poor dispersibility, it is also easy to analyze the cause of defects, and as mentioned above, there is an advantage in terms of quality control. In addition, in the case of the batch type, there is an advantage that there are fewer factors to consider when moving from small-scale development consideration to mass production. For the same reason, it is also preferable in terms of productivity and quality control to perform process (A) and process (B) using the same container and the same planetary mixing device. It is expected that the influence of contamination can also be suppressed. In the case of mass production, it is only necessary to increase the number of the same devices. In other words, it is possible to handle small-scale production of many different types of products and to scale up. Therefore, it is also easy to adjust production management.
[0045] In addition, covering the surface of the large-diameter filler with a sufficiently small small-particle filler is preferable in terms of maintaining the quality of the surface state of the conductive particles when the conductive particles, which are large-diameter particles, are sandwiched between terminals, such as in anisotropic conductive connection described below. In other words, it is expected that the small-particle filler will cover and intervene to protect the irregularity of the surface state caused by contact between large-diameter particles. In addition, since the coating is only removed by mixing (kneading), it is unlikely that the partial coating will hinder conduction if a direct force such as being sandwiched between terminals is applied to the large-diameter particles. In addition, in terms of insulation between terminal arrangements, the large-diameter particles maintain high dispersibility, but at the same time, they also maintain partial coating, so it is thought that short circuits (caused by large-diameter particles being connected together) are easily avoided. To give an example of a specific effect, in the case of conductive particles in which the large-diameter particles are metal-plated resin particles, it is expected that the range of choices for the thickness and material of the metal plating, the hardness of the resin particles, etc. will be wider than before. The same can be said for products that are used by being sandwiched, such as spacers.
[0046] The method for stirring the first coated particles and the insulating binder is not particularly limited, and the stirring method in the above-mentioned step (A) can be used. In particular, from the viewpoint of separating the small particle size filler constituting the first coated particles when the first coated particles and the insulating binder are stirred, a stirring method that applies a high shear, for example, a stirring method using a planetary stirring device, is preferred. It is considered that the use of a planetary stirring device causes friction and high shear between the large particle size particles and the small particle size filler in the first coated particles in the insulating binder, resulting in appropriate separation of the small particle size filler from the large particle size particles in the first coated particles.
[0047] According to the manufacturing method having the above steps (A) and (B), a resin composition in which the second coated particles are dispersed in the insulating binder can be obtained in a simple manner. Note that, this manufacturing method may further include other steps in addition to the above steps (A) and (B) as necessary. Note that, as described above, it is preferable in terms of productivity and quality to carry out steps (A) and (B) in the same container and the same device (planetary stirring type mixer).
[0048] <Structure> In the structure according to the present embodiment, the first member and the second member are bonded via the above-mentioned resin composition. If the resin composition is a curable resin, it may be cured and fixed, or if it is an adhesive, it may simply be pasted. This is one example, and for example, the resin composition may be filled into a mold and cured to obtain a molded body. For example, when the resin composition is made to function as a spacer between the first member and the second member, the amount of small particle diameter filler attached to the large particle is small, so that the spacer can be made to have an approximate diameter of the large particle. In addition, for example, when the resin composition is made into a conductive adhesive in which the large particle is a conductive particle and the small particle diameter filler is an insulating filler, the amount of insulating filler attached to the conductive particle is small, so that excellent conductivity can be obtained. When it is made into an anisotropic conductive adhesive, the relationship between the terminal and the terminal arrangement acts more complexly, so that this effect can be more effectively exhibited. In addition, these may be made into a film body in advance.
[0049] The present invention also includes a structure in which the resin composition is used as an adhesive or adhesive film to connect a first article and a second article, and a manufacturing method thereof. These articles may be electronic components, and may have a conductive portion (anisotropy is not essential) and have electrical conductivity, but are not limited thereto. The present invention also includes a first article and a second article bonded together, regardless of whether the resin composition has adhesive properties or not, and a bonding method thereof. In other words, it is a bonded body of a first article and a second article, and a bonding method in which these are pressed. The present invention also includes a resin composition or a film body thereof provided only on the first article. This can be done by applying the resin composition or bonding it as a film body to the first article. If the resin composition is an adhesive body, an adhesive layer will be formed. It can also be made into an adhesive film by forming it on a support.
[0050] The second embodiment will now be described. [Second embodiment]
[0051] <Anisotropic conductive adhesive> The anisotropic conductive adhesive according to the present embodiment contains coated conductive particles (second coated conductive particles described later) in which a portion of the surface of the conductive particle is coated with an insulating filler, an insulating filler, and an insulating binder, and the coated conductive particles are dispersed in the insulating binder. In the following description, the coated conductive particles in which the conductive particles are coated with the insulating filler, obtained by stirring the conductive particles having an average particle size of 7 μm or more and the insulating filler, are referred to as "first coated conductive particles". In addition, the coated conductive particles in which a portion of the surface of the conductive particle is coated with the insulating filler, obtained by stirring the first coated conductive particles and the insulating binder, are referred to as "second coated conductive particles".
[0052] The anisotropic conductive adhesive may be either a film-like anisotropic conductive film (ACF: Anisotropic Conductive Film) or a paste-like anisotropic conductive paste (ACP: Anisotropic Conductive Paste). From the viewpoint of ease of handling, the anisotropic conductive film is preferred. From the standpoint of cost, anisotropic conductive paste is preferable.
[0053] The second coated conductive particles (conductive particles, insulating filler), insulating binder, and other components that may be further contained, which constitute the anisotropic conductive adhesive, will be described below.
[0054] [Conductive particles] The material of the conductive particles is not particularly limited. For example, metal particles such as nickel, copper, gold, silver, and palladium, and metal-coated resin particles in which the surface of resin particles is coated with a metal can be mentioned. As the resin particles in the metal-coated resin particles, for example, particles of epoxy resin, phenol resin, acrylic resin, acrylonitrile-styrene resin, benzoguanamine resin, divinylbenzene resin, and styrene resin can be used. The conductive particles may be used alone or in combination of two or more kinds.
[0055] The conductive particles have a particle diameter of 7 μm or more. The upper limit of the conductive particle diameter is not particularly limited, but is preferably 50 μm or less from the viewpoint of the capture efficiency of the conductive particles in the connection structure. The conductive particle diameter can be measured by an image type particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Instruments). It is desirable to measure 1000 particles or more, preferably 2000 particles or more.
[0056] [Insulating filler] The insulating filler may be an insulating inorganic particle. For example, oxides such as titanium oxide, aluminum oxide, silica, calcium oxide, and magnesium oxide, hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, magnesium carbonate, zinc carbonate, and barium carbonate, sulfates such as calcium sulfate and barium sulfate, silicates such as calcium silicate, and nitrides such as aluminum nitride, boron nitride, and silicon nitride. The insulating filler may be used alone or in combination of two or more.
[0057] Regarding the relationship between the size (particle diameter) of the conductive particles and the insulating filler, the insulating filler is extremely small compared to the surface area of the conductive particles, so that the insulating filler can easily cover and separate from the surface of the conductive particles. As a result, when the first coated conductive particles are stirred in the insulating binder, the insulating filler that has separated from the conductive particles in the first coated conductive particles is interposed between the second coated conductive particles, so that the aggregation of the second coated conductive particles can be suppressed. Therefore, the second coated conductive particles can be uniformly dispersed in the insulating binder.
[0058] Specifically, the upper limit of the particle size of the insulating filler is preferably 1000 nm or less, more preferably 50 nm or less. When the insulating filler is not too large compared to the surface area of the conductive particles, defects such as scratches on the surface of the conductive particles can be suppressed. In addition, the lower limit of the particle size of the insulating filler is preferably 10 nm or more. When the insulating filler is not too small compared to the surface area of the conductive particles, aggregation of the conductive particles can be more effectively suppressed. The particle size of the insulating filler can be determined from the results of observation using an electron microscope or the like.
[0059] Due to the size relationship between the conductive particles and the insulating filler described above, the ratio of particle diameters of the conductive particles and the insulating filler (particle diameter of insulating filler / particle diameter of conductive particles) is 0.02 to 0.143%, and preferably 0.02 to 0.10%.
[0060] Furthermore, the ratio of the number of insulating fillers to the conductive particles that satisfies the above-mentioned particle size ratio, i.e., the amount of insulating filler to one conductive particle, is 0.78 to 77 volume %, preferably 3.9 to 38.7 volume %, and more preferably 7.7 to 15.5 volume %. By satisfying such conditions, the dispersibility of the conductive particles can be improved.
[0061] [Insulating binder] The insulating binder (insulating resin) may be an insulating binder used in a known anisotropic conductive adhesive. Examples of the curing type include a heat curing type, a photocuring type, and a photo-thermal combined curing type. Examples include a photoradical polymerization type resin containing a (meth)acrylate compound and a photoradical polymerization initiator, a thermal radical polymerization type resin containing a (meth)acrylate compound and a thermal radical polymerization initiator, a thermal cationic polymerization type resin containing an epoxy compound and a thermal cationic polymerization initiator, and a thermal anionic polymerization type resin containing an epoxy compound and a thermal anionic polymerization initiator.
[0062] In the following, a specific example will be described, taking as an example a thermal anionic polymerization type insulating binder containing a film-forming resin, an epoxy resin, and a latent curing agent.
[0063] The film-forming resin is preferably a resin having an average molecular weight of about 10,000 to 80,000. Examples of the film-forming resin include various resins such as epoxy resin, modified epoxy resin, urethane resin, and phenoxy resin. Among these, phenoxy resin is preferred from the viewpoint of film formation state, connection reliability, etc. The film-forming resin may be used alone or in combination of two or more kinds.
[0064] The epoxy resin is not particularly limited, but examples thereof include naphthalene type epoxy resin, biphenyl type epoxy resin, phenol novolac type epoxy resin, bisphenol type epoxy resin, stilbene type epoxy resin, triphenolmethane type epoxy resin, phenol aralkyl type epoxy resin, naphthol type epoxy resin, dicyclopentadiene type epoxy resin, triphenylmethane type epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more kinds.
[0065] Examples of latent curing agents include imidazole-based, hydrazide-based, amine imide, dicyandiamide, or acid generators such as antimony-based, phosphorus-based, and fluorine-based. These can be used alone or in combination of two or more. Among these, a microcapsule type in which the surface of imidazole compound particles is covered with a polymer cured product such as a polyurethane or polyester-based product is preferably used. In addition, a masterbatch type curing agent in which a microcapsule type curing agent is dispersed in a liquid epoxy resin may be used.
[0066] [Other ingredients] The anisotropic conductive adhesive may further contain other components in addition to the second coated conductive particles and the insulating binder, as necessary. Examples of the other components include a solvent (methyl ethyl ketone, toluene, propylene glycol monomethyl ether acetate, etc.), a stress relaxation agent, a silane coupling agent, etc. The anisotropic conductive adhesive may further contain an insulating filler that is separated from the conductive particles in the first coated conductive particles.
[0067] As described above, the anisotropic conductive adhesive has conductive particles with a particle diameter of 7 μm or more, insulating filler particles with a particle diameter of 0.02 to 0.143% of the conductive particle diameter, and the amount of insulating filler relative to the conductive particles is 0.78 to 77% by volume. When the first coated conductive particles are stirred in the insulating binder, they are separated from the conductive particles in the first coated conductive particles. Therefore, there are cases where the second coated conductive particles have the coated insulating filler remaining on the particle surface, and such a remaining state can be confirmed by a known observation method (electron microscope such as SEM or TEM). It can be confirmed whether the product is obtained by the method of the present invention by the remaining state of the insulating filler and the dispersion state of the conductive particles.
[0068] In the anisotropic conductive adhesive, the insulating filler separated from the conductive particles in the first coated conductive particles is interposed between the second coated conductive particles, so that the aggregation of the second coated conductive particles can be suppressed. Therefore, the second coated conductive particles can be dispersed in the insulating binder, and short circuits between the electrode terminals of the electronic component can be suppressed. In addition, in the anisotropic conductive adhesive, the insulating filler separated from the conductive particles in the first coated conductive particles by stirring the first coated conductive particles and the insulating binder is uniformly present at a certain ratio near the second coated conductive particles in the insulating binder. In such an anisotropic conductive adhesive, there is a high correlation between the dispersion state of the second coated conductive particles and the region where the insulating filler is present, so that the conductive particle capture rate can be stabilized.
[0069] In addition, in this technology, a relatively large conductive particle of 7 μm or more is simply coated with an insulating filler, and the insulating filler is dissociated when kneaded with an insulating binder, so that a sufficient effect of suppressing short circuits can be obtained without previously insulating the surface (conductive layer) of the conductive particle. That is, there are no traces of the insulating treatment except for the insulating filler that remains in a small amount without dissociating in the conductive layer of the conductive particle. Therefore, the conductive particle is easy to handle and is advantageous in terms of cost. In the design of anisotropic conductive adhesives, the number of parameters is reduced, which is advantageous in terms of development. In addition, by using conductive particles that have been previously insulated by a known method, it is possible to improve performance by using conductive particles with better insulating properties and increase the degree of freedom in design. Therefore, this technology does not exclude the use of conductive particles whose surfaces (conductive layers) have been previously insulated.
[0070] <Manufacturing method of anisotropic conductive adhesive> The method for producing an anisotropic conductive adhesive according to the present embodiment includes the following steps (A) and (B).
[0071] [Process (A)] In step (A), conductive particles having an average particle size of 7 μm or more and insulating filler having a particle size of 0.02 to 0.143% of the particle size of the conductive particles are stirred to obtain first coated conductive particles. In step (A), the conductive particles are coated with insulating filler in order to suppress aggregation of the second coated conductive particles obtained in step (B). In addition, in step (A), as described above, the conductive particles and the insulating filler are mixed so that the amount of insulating filler relative to the conductive particles is 0.78 to 77 volume %. By satisfying such conditions, the coating of the insulating filler on the surfaces of the conductive particles can be easily progressed in step (A), and the insulating filler in the first coated conductive particles can be easily separated in step (B).
[0072] The method of stirring the conductive particles and the insulating filler may be either a dry method or a wet method, with the dry method being preferred. Examples of devices for stirring the conductive particles and the insulating filler include planetary stirring devices, shakers, lab mixers, stirring propellers, and the like. In particular, from the viewpoint of coating the conductive particles with a relatively large average particle size with the insulating filler, a planetary stirring device with a high shear is preferred. The planetary stirring device refers to a stirring device that rotates and revolves a container containing a material (a mixture of conductive particles and insulating filler) on its axis.
[0073] The conductive particles and insulating filler have the same preferred ranges as those described for the anisotropic conductive adhesive. In particular, it is preferable to use conductive particles in a dry powder state from the viewpoint of coating the conductive particles with the insulating filler in step (A).
[0074] [Process (B)] In step (B), the first coated conductive particles and the insulating binder are stirred to obtain an anisotropic conductive adhesive in which the second coated conductive particles and the insulating filler that has separated from the conductive particles in the first coated conductive particles are dispersed in the insulating binder.
[0075] In step (B), the first coated conductive particles are stirred in the insulating binder, and friction and high shear between the insulating filler in the first coated conductive particles and the conductive particles causes the insulating filler to separate from the conductive particles, resulting in coated conductive particles (second coated conductive particles) in which a portion of the surface of the conductive particle is coated with the insulating filler. In addition, the insulating filler that has separated from the conductive particles in the first coated conductive particles is interposed between the second coated conductive particles, so that aggregation of the second coated conductive particles can be suppressed. Thus, by performing step (B), aggregation of the second coated conductive particles can be suppressed, and the second coated conductive particles can be dispersed in the insulating binder.
[0076] The method for stirring the first coated conductive particles and the insulating binder is not particularly limited, and the stirring method in the above-mentioned step (A) can be adopted. In particular, from the viewpoint of dissociating the insulating filler constituting the first coated conductive particles when the first coated conductive particles and the insulating binder are stirred, a stirring method that applies a high shear, for example, a stirring method using a planetary stirring device, is preferred. By using a planetary stirring device, friction or high shear is applied between the conductive particles and the insulating filler in the first coated conductive particles, which may cause the insulating filler to dissociate from the conductive particles in the first coated conductive particles.
[0077] According to the manufacturing method including the above steps (A) and (B), an anisotropic conductive adhesive in which the second coated conductive particles are dispersed in an insulating binder can be obtained in a simple manner. By using this anisotropic conductive adhesive, it is possible to suppress short circuits between electrode terminals of electronic components. Furthermore, if steps (A) and (B) are performed in the same container and the same device (planetary stirring type mixer), this is preferable in terms of manufacturing man-hours and quality control such as preventing contamination.
[0078] Incidentally, the present production method may further include a step other than the above-mentioned step (A) and step (B) as necessary.
[0079] <Anisotropic conductive film> The anisotropic conductive film according to the present embodiment is made of the above-mentioned anisotropic conductive adhesive, and the above-mentioned second coated conductive particles are dispersed in an adhesive layer made of an insulating binder. For example, the number density (number / mm 2 ) of the second coated conductive particles in the entire anisotropic conductive film (e.g., 1.0 mm×1.0 mm) is 2 ) and a small area arbitrarily extracted in the anisotropic conductive film (e.g., 0.2 mm × 0.2 mm) 2 ) is preferably 15% or less, more preferably 10% or less, It is even more preferable that the dispersibility is substantially the same (for example, within 5%). When used for connection as an anisotropic conductive paste, for example, it is preferable that the dispersibility is similar to that described above. This can be confirmed by forming a layer on a smooth surface such as a support.
[0080] In this way, the difference between the number density of the second coated conductive particles in the entire anisotropic conductive film and the number density of the second coated conductive particles in an arbitrarily extracted narrow region of the anisotropic conductive film is small, so that it can be confirmed that the second coated conductive particles are uniformly dispersed throughout the entire film. Therefore, the conductive particle capture rate is stable, and poor conduction and short circuits can be suppressed. When the second coated conductive particles are uniformly dispersed throughout the entire film, there is an effect that the man-hours for the quality inspection of the anisotropic conductive film itself can be reduced. This is because irregular aggregation is easily found when the particles are uniformly dispersed. Therefore, the effect is particularly enhanced when the length is 10 m or more. In addition, if the anisotropic conductive film is 10 m or more, preferably 50 m or more, continuous connection can be performed, which has the effect of reducing the cost of the manufacturing method of the connection structure. There is no particular upper limit on the length, but from the viewpoint of minimizing the improvement of the connection device and handling, it is preferably 5000 m or less, more preferably 1000 m or less, and even more preferably 600 m or less.
[0081] In addition, when the conductive particle diameter is relatively large, such as 7 μm or more, as in the present invention, it is suitable for connecting electronic components such as ceramic substrates whose surfaces are not as smooth as glass (surfaces that have undulations). In addition, because the relatively large conductive particles are uniformly dispersed in this manner, even if the electronic components to be connected have undulations, they are less susceptible to capture due to the flow of resin during connection. This is because, when the conductive particles are aggregated, the terminal surface on which the conductive particles are captured due to the undulations is not constant, and there is a concern that the capture state for each terminal cannot be kept constant.
[0082] The particle density of the second coated conductive particles in the anisotropic conductive film is not particularly limited as long as it can achieve both electrical conductivity reliability and short circuit prevention. For example, if the particle density is too small, it becomes difficult to satisfy electrical conductivity reliability. Therefore, the particle density is set to 20 particles / mm 2 More than 100 pieces / mm is preferable. 2 More preferably, the upper limit is set to 3000 pieces / mm. 2 Preferably less than 2000 pieces / mm 2 Less than 1000 pieces / mm is more preferable. 2 The following is more preferable. These may be adjusted appropriately depending on the conductive particle diameter and the size of the terminal to be connected. In addition, when an anisotropic conductive paste is used, the same as above is preferable as an example. This can be confirmed by forming a layer on a smooth surface such as a support.
[0083] The upper limit of the area occupancy of the second coated conductive particles in the anisotropic conductive film in plan view is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less. Such a high area occupancy is achieved because the second coated conductive particles are kneaded into the insulating resin with high uniformity, depending on the ratio of the thickness and particle diameter of the anisotropic conductive film. It can be said that one of the features of the present invention is that the risk of short circuit occurrence can be avoided even with such a high area occupancy. In addition, when used as an anisotropic conductive paste for connection, it is preferable to obtain the same dispersibility as described above, for example. This can be confirmed by forming a layer on a smooth surface such as a support.
[0084] The lower limit of the area occupancy rate of the second coated conductive particles in the anisotropic conductive film in plan view depends on the ratio of the thickness of the anisotropic conductive film to the particle diameter, but for example, if it is more than 0.2%, a minimum conductive performance can be ensured, and more than 5% is practically preferable, and more preferably more than 10%. In addition, when an anisotropic conductive paste is used, the same as above is preferable, for example. This can be confirmed by forming a layer on a smooth surface such as a support.
[0085] The area occupancy rate of the second coated conductive particles in the anisotropic conductive film in plan view can be calculated based on observation with an optical microscope, a metallurgical microscope, or an electron microscope such as a SEM. It may be measured using a known image analysis software (an example is WinROOF (Mitani Shoji Co., Ltd.)). The area for calculating the area occupancy rate may be the same as an example of the area for determining the number density, or may be determined using a larger area (for example, 2 mm x 2 mm or 5 mm x 5 mm). When used for connection as an anisotropic conductive paste, it is preferable, for example, to obtain the same dispersibility as described above. This can be confirmed by forming a layer on a smooth surface such as a support.
[0086] The method of forming the anisotropic conductive film includes, for example, forming a film of an anisotropic conductive adhesive by coating and drying it. The thickness of the anisotropic conductive film may have a lower limit equal to the particle diameter, and is preferably 1.3 times or more the particle diameter or 10 μm or more. For example, the upper limit may be 40 μm or less or 2 times or less the particle diameter. The anisotropic conductive film may be formed on a release film.
[0087] <Connection structure> In the connection structure according to the present embodiment, a first electronic component and a second electronic component are connected via the above-mentioned anisotropic conductive film. For example, as shown in Fig. 1, in the connection structure 1, a first electronic component 5 having a first terminal row 4 consisting of a plurality of terminals 4a and a second electronic component 7 having a second terminal row 6 facing the first terminal row 4 and consisting of a plurality of terminals 6a are connected via conductive particles (second coated conductive particles) 3 in an anisotropic conductive film 2.
[0088] The first electronic component and the second electronic component are not particularly limited and can be appropriately selected depending on the purpose. Examples of the first electronic component include flexible printed circuits (FPCs) and transparent substrates. The transparent substrate can be any substrate as long as it is highly transparent. There is no particular limitation, and examples thereof include a glass substrate and a plastic substrate. Examples of the second electronic component include a camera module, an IC (Integrated Circuit) module, and an IC chip. The second electronic component may be a functional module equipped with a sensor. In a camera module, a ceramic substrate may be used because of its excellent electrical insulation and thermal insulation properties. Ceramic substrates and functional modules are often used for miniaturization (for example, 1 cm 2 It has the advantages of excellent dimensional stability at low temperatures (see below).
[0089] <Method of Manufacturing Connection Structure> The method for manufacturing the connection structure according to the present embodiment includes crimping a first electronic component 5 having a first terminal row 4 and a second electronic component 7 having a second terminal row 6 opposing the first terminal row 4 via the above-mentioned anisotropic conductive film. This allows the first terminal row 4 and the second terminal row 6 to be connected via the conductive particles 3.
[0090] The first electronic component 5 and the second electronic component 7 are similar to the first electronic component 5 and the second electronic component 7 in the connection structure described above. The anisotropic conductive adhesive is also similar to the anisotropic conductive adhesive described above. EXAMPLES
[0091] A first embodiment of the present technology will be described below.
[0092] [Experimental Example 1] [Preparation of anisotropic conductive adhesive (resin composition)] Conductive particles with an average particle size of 3 μm (large particle size, Ni plating (thickness 115 nm), resin core, specific gravity 3.44 g / cm 3 ) and a silica filler with an average particle size of 10 nm (small particle size filler, product name: YA010C, specific gravity 2.2 g / cm 30.5 g (78.2 volume % relative to the conductive particles) was placed in a planetary mixing device (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for 5 minutes to produce a mixture of conductive particles and insulating filler.
[0093] The proportion of the number of insulating fillers was evaluated as either "appropriate," "excessive," or "insufficient." Specifically, the proportion of the number of silica fillers relative to the conductive particles, i.e., the amount of silica filler relative to the conductive particles, was evaluated as "appropriate." Furthermore, the amount of silica filler relative to the conductive particles was evaluated as "excessive" when it exceeded 156% by volume. Furthermore, the amount of silica filler relative to the conductive particles was evaluated as "insufficient" when it exceeded 1.56% by volume.
[0094] The mixture of conductive particles and insulating filler and an insulating binder consisting of the following components were added to a planetary mixer (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for 1 minute to produce an anisotropic conductive adhesive.
[0095] The insulating binder was prepared by mixing 20 g of epoxy resin (EP828, manufactured by Mitsubishi Chemical Corporation), 30 g of phenoxy resin (YP-50, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.), and 50 g of a curing agent (Novacure 3941HP, manufactured by Asahi Kasei Corporation) diluted with toluene.
[0096] [Preparation of anisotropic conductive film (film body)] The anisotropic conductive adhesive was applied to a PET film and dried in an oven at 80°C for 5 minutes to form an adhesive layer made of the anisotropic conductive adhesive on the PET film. This resulted in an anisotropic conductive film with a thickness of 12 μm (four times the particle size of the large particles). The number density of the conductive particles in the anisotropic conductive film was approximately 5,000 particles / mm 2 It was adjusted so that
[0097] [Experimental Example 2] An anisotropic conductive film was produced and evaluated in the same manner as in Experimental Example 1, except that the amount of insulating filler was changed to 0.15 g (23.5% by volume relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0098] [Experimental Example 3] An anisotropic conductive film was produced and evaluated in the same manner as in Experimental Example 1, except that the amount of insulating filler was changed to 0.05 g (7.8 volume % relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0099] [Experimental Example 4] An anisotropic conductive film was produced and evaluated in the same manner as in Experimental Example 1, except that an anisotropic conductive adhesive was produced without blending an insulating filler.
[0100] [Experimental Example 5] An anisotropic conductive film was produced and evaluated in the same manner as in Experimental Example 1, except that the amount of insulating filler was changed to 1 g (156% by volume relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0101] [Experimental Example 6] An anisotropic conductive film was produced and evaluated in the same manner as in Experimental Example 1, except that the amount of insulating filler was changed to 0.01 g (1.56 volume % relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0102] [With or without insulating filler] The cross-sections of the conductive particles in the anisotropic conductive film were observed with a scanning electron microscope to confirm whether or not the insulating filler was attached to the surface of the conductive particles. Cases where the insulating filler was attached to the surface of the conductive particles were rated as "present," and cases where the insulating filler was not attached were rated as "absent." The results are shown in Table 1.
[0103] [Difference in number density of conductive particles] The number density of conductive particles (particles / mm 2 ) and 10 randomly selected 0.2 mm × 0.2 mm squares were taken from the anisotropic conductive film. Conductive particle number density in the area (number / mm 2 ) was evaluated. The evaluation criteria are as follows. A or B is preferable. The results are shown in Table 1. The difference in number density is the difference between the maximum and minimum values of the number density of conductive particles in a given area arbitrarily extracted. A: The difference in density is 10% or less B: The difference in number density is greater than 10 and less than 15% C: The difference in density is greater than 15%
[0104] [Fabrication of connection structure] A flexible substrate (copper wiring: line / space (L / S) = 25 μm / 25 μm, terminal height: 8 μm, polyimide thickness: 25 μm) and ITO solid glass (thickness: 0.7 mm) were heated and pressed (180°C, 2 MPa, 20 seconds) using the anisotropic conductive film prepared by a heating and pressing member to obtain a connection structure.
[0105] [Initial resistance value] Using a digital multimeter (manufactured by Yokogawa Electric Corporation), the conductive resistance value of the connection structure was measured when a current of 1 mA was applied using the four-terminal method. A conductive resistance value of the connection structure of less than 2.0 Ω was evaluated as "OK", and a conductive resistance value of 2.0 Ω or more was evaluated as "NG". All of the experimental examples 1 to 3 were OK.
[0106] [Resistance value after connection reliability test] The connection structure was left for 1000 hours in an atmosphere of 60°C and 95% relative humidity, and then the conductive resistance value of this connection structure was measured in the same manner as the initial resistance value. The evaluation criteria were that a conductive resistance value of less than 5.0Ω was evaluated as "OK" and a conductive resistance value of 5.0Ω or more was evaluated as "NG". All of the experimental examples 1 to 3 were OK.
[0107] [Number of captured conductive particles] Regarding the connection structure samples, it was confirmed that a sufficient number of conductive particles were captured by the opposing terminals in Experimental Examples 1 to 3. In addition, when the capture state was compared between Experimental Examples 1 to 3 and Experimental Examples 4 to 6, Experimental Examples 1 to 3 showed a tendency for the number of captured particles in each bump to be more uniform.
[0108] [short] A connection structure similar to that used in the evaluation of the initial resistance value was fabricated, and the occurrence of short circuits between adjacent terminals was evaluated. When the short circuit occurrence rate was 50 ppm or less, it was evaluated as "OK", and when the short circuit occurrence rate exceeded 50 ppm, it was evaluated as "NG". All of the results were OK in Experimental Examples 1 to 3. [Table 1]
[0109] In Experimental Examples 1 to 3, it was found that the difference in number density of the conductive particles (second coated conductive particles) in the anisotropic conductive film can be reduced by setting the amount of insulating filler, whose particle diameter is 0.02% or more and 5.0% or less of the conductive particle diameter, to more than 1.56 volume % and less than 156 volume % relative to the conductive particles and stirring the conductive particles and insulating filler. In particular, it was found from Experimental Examples 1 to 3 that a good state can be obtained by setting the amount to 7.8 to 78.2 volume %. In other words, it was found that the dispersibility of the conductive particles is good.
[0110] In Experimental Examples 1 to 3, the conductive particles in the cross section of the film were observed using SEM images, and the state of coating with the insulating filler was confirmed. In the second coated conductive particles in the insulating binder obtained in this manner, a part of the coating of the insulating filler may remain. The remaining coating of the insulating filler on the surface of the conductive particles was confirmed by observing the second coated conductive particles according to Experimental Examples 1 to 3 using an electron microscope (SEM).
[0111] In addition, it was found that short circuits between electrode terminals of electronic components could be suppressed in Experimental Examples 1 to 3. Furthermore, it was found that the conductive particle capture rate was good in Experimental Examples 1 to 3, and the evaluations of the initial resistance value and the resistance value after the reliability test were also good. It was also found that the dispersibility of the conductive particles was particularly good in Experimental Examples 1 and 2.
[0112] In Experimental Example 4, in which no insulating filler having a particle diameter of 0.02 to 5.0% of the particle diameter of the conductive particles was blended, it was found that the difference in number density of the conductive particles could not be reduced. That is, it was found that the dispersibility of the conductive particles was not good in Experimental Example 4. It was also found that in Experimental Example 4, short circuits between electrode terminals of electronic components could not be suppressed, and the conductive particle capture rate was not good. It was also found that in Experimental Example 4, the evaluations of both the initial resistance value and the resistance value after the reliability test were not good, compared with Examples 1 to 3.
[0113] In Experimental Example 5, in which the amount of insulating filler with a particle diameter of 0.02 to 0.5% of the conductive particle diameter was set to 156 volume % relative to the conductive particles, it was found that the difference in number density of the conductive particles could not be reduced. That is, in Experimental Example 5, the number ratio of insulating filler with a particle diameter of 0.02 to 0.5% of the conductive particle diameter was excessive, so that the dispersibility of the conductive particles was not good. In addition, in Experimental Example 5, it was found that short circuits between electrode terminals of electronic components could not be suppressed, and the conductive particle capture rate was not good. In addition, in Experimental Example 5, it was found that the evaluation of both the initial resistance value and the resistance value after the reliability test were not good compared to Examples 1 to 3.
[0114] In Experimental Example 6, in which the amount of insulating filler with a particle diameter of 0.02 to 0.5% of the conductive particle diameter was set to 1.57 volume % relative to the conductive particles, it was found that the difference in number density of the conductive particles could not be reduced. That is, in Experimental Example 6, it was found that the dispersibility of the conductive particles was not good because the number ratio of the insulating filler with a particle diameter of 0.02 to 0.5% of the conductive particle diameter was insufficient. In addition, it was found that in Experimental Example 6, short circuits between electrode terminals of electronic components could not be suppressed and the conductive particle capture rate was not good compared to Examples 1 to 3.
[0115] A second embodiment of the present technology will be described below.
[0116] [Example 1] [Preparation of anisotropic conductive adhesive] Conductive particles with an average particle size of 20 μm (Au plating (outer layer, thickness 34 nm) / Ni plating (inner layer, thickness 200 nm), resin core, specific gravity 1.4 g / cm 3 ) and silica filler with an average particle size of 10 nm (product name: YA010C, specific gravity 2.2 g / cm 3 0.5 g (38.7 volume % relative to the conductive particles) was added to a planetary mixing device (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for 5 minutes to produce a mixture of conductive particles and insulating filler.
[0117] The ratio of the number of insulating fillers was evaluated as either "appropriate amount," "excessive," or "insufficient." Specifically, the ratio of the number of silica fillers to the conductive particles, i.e., the amount of silica filler relative to the conductive particles, was evaluated as "appropriate amount." Furthermore, the amount of silica filler relative to the conductive particles was evaluated as "excessive" when it exceeded 77% by volume. Furthermore, the amount of silica filler relative to the conductive particles was evaluated as "insufficient" when it was less than 0.78% by volume.
[0118] The mixture of conductive particles and insulating filler and an insulating binder consisting of the following components were added to a planetary mixer (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for 1 minute to produce an anisotropic conductive adhesive.
[0119] The insulating binder was prepared by diluting and mixing 20 g of epoxy resin (EP828, manufactured by Mitsubishi Chemical Corporation), 30 g of phenoxy resin (YP-50, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.), and 50 g of hardener (Novacure 3941HP, manufactured by Asahi Kasei Corporation) with toluene.
[0120] [Preparation of anisotropic conductive film] The anisotropic conductive adhesive was applied to a PET film and dried in an oven at 80°C for 5 minutes to form an adhesive layer made of the anisotropic conductive adhesive on the PET film. This resulted in an anisotropic conductive film with a thickness of 25 μm. The number density of conductive particles in the anisotropic conductive film was approximately 300 particles / mm 2 It was adjusted so that
[0121] [With or without insulating filler] The cross-sections of the conductive particles in the anisotropic conductive film were observed with a scanning electron microscope to confirm whether or not the insulating filler was attached to the surface of the conductive particles. Cases where the insulating filler was attached to the surface of the conductive particles were rated as "present," and cases where the insulating filler was not attached were rated as "absent." The results are shown in Table 2.
[0122] [Difference in number density of conductive particles] The number density of conductive particles (particles / mm 2 ) and 10 randomly selected 0.2 mm × 0.2 mm squares were taken from the anisotropic conductive film. Conductive particle number density in the area (number / mm 2 ) was evaluated. The evaluation criteria are as follows. A or B is preferable. The difference in number density is the difference between the maximum and minimum values of the number density of conductive particles in a given area arbitrarily extracted. The results are shown in Table 2. A: The difference in density is 10% or less B: The difference in number density is greater than 10 and less than 15% C: The difference in density is greater than 15%
[0123] [Fabrication of connection structure] A flexible substrate (copper wiring: line / space (L / S) = 100 μm / 100 μm, terminal height: 12 μm, polyimide thickness: 25 μm) and an alumina ceramic substrate (gold / tungsten wiring: line / space (L / S) = 100 μm / 100 μm, wiring height: 10 μm, substrate thickness: 0.4 mm) were heated and pressed (180°C, 1 MPa, 20 seconds) using the anisotropic conductive film prepared by a heating and pressing member to obtain a connection structure.
[0124] [Initial resistance value] Using a digital multimeter (manufactured by Yokogawa Electric Corporation), the conductive resistance value of the connection structure was measured when a current of 1 mA was applied using the four-terminal method. A conductive resistance value of the connection structure of less than 1.0 Ω was rated as "OK", and a conductive resistance value of 1.0 Ω or more was rated as "NG". The results are shown in Table 2.
[0125] [Resistance value after connection reliability test] The connection structure was left for 1000 hours in an atmosphere of 60°C and 95% relative humidity, and then the conductive resistance of this connection structure was measured in the same manner as for the initial resistance. The evaluation criteria were the same as for the initial resistance. The results are shown in Table 2.
[0126] [Number of captured conductive particles] For the connection structure samples, the number of conductive particles captured by the opposing terminals was counted, and the average number of conductive particles captured for a total of 150 terminals was calculated, and this average value was evaluated according to the following criteria. The evaluation criteria are as follows. A or B is preferable. The results are shown in Table 2. A: 5 or more B: 3~4 pieces C: Less than 2
[0127] [short] A connection structure similar to that used in the evaluation of the initial resistance value was fabricated and evaluated for the occurrence of short circuits between adjacent terminals. A short circuit occurrence rate of 50 ppm or less was evaluated as "OK", and a short circuit occurrence rate of more than 50 ppm was evaluated as "NG". The results are shown in Table 2.
[0128] [Example 2] An anisotropic conductive film was produced and evaluated in the same manner as in Example 1, except that the amount of insulating filler was changed to 0.15 g (11.6% by volume relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0129] [Example 3] An anisotropic conductive film was produced and evaluated in the same manner as in Example 1, except that the amount of insulating filler was changed to 0.05 g (3.9% by volume relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0130] [Comparative Example 1] An anisotropic conductive film was produced and evaluated in the same manner as in Example 1, except that an anisotropic conductive adhesive was produced without blending an insulating filler.
[0131] [Comparative Example 2] An anisotropic conductive film was produced and evaluated in the same manner as in Example 1, except that the amount of insulating filler was changed to 1.0 g (77.3% by volume relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0132] [Comparative Example 2] An anisotropic conductive film was produced and evaluated in the same manner as in Example 1, except that the amount of insulating filler was changed to 0.01 g (0.77 volume % relative to the conductive particles) to produce an anisotropic conductive adhesive.
[0133] [Table 2]
[0134] In the examples, the amount of insulating filler with a particle diameter of 0.02 to 0.143% of the conductive particle diameter was set to 0.78 to 77 volume % relative to the conductive particles, and the conductive particles and the insulating filler were stirred, whereby it was found that the difference in number density of the conductive particles (second coated conductive particles) in the anisotropic conductive film could be reduced. In particular, it was found from the examples that a good state could be obtained by setting the amount to 3.9 to 38.7 volume %. That is, it was found that the dispersibility of the conductive particles was good. Also, it was found from the examples that a short circuit between electrode terminals of an electronic component could be suppressed. Furthermore, it was found that the conductive particle capture rate was good, and the evaluation of the initial resistance value and the resistance value after a reliability test were also good. In particular, it was found that the dispersibility of the conductive particles was better in Examples 1 and 2.
[0135] In the embodiment, the conductive particles and the insulating filler are stirred to obtain the first coated conductive particles 10 as shown in FIG. 2. The first coated conductive particles 10 are stirred in the insulating binder to separate the silica filler from the conductive particles in the first coated conductive particles 10, and the second coated conductive particles 11 are obtained as shown in FIG. 3. The separated silica filler is interposed between the second coated conductive particles 11. This suppresses the aggregation of the second coated conductive particles 11, and the second coated conductive particles 11 can be uniformly dispersed in the insulating binder. In the second coated conductive particles 11 in the insulating binder obtained in this manner, a part of the coating of the insulating filler may remain. The remaining coating of the insulating filler on the conductive particle surface could be confirmed by observing the second coated conductive particles 11 according to Examples 1 to 3 with an electron microscope (SEM).
[0136] It was found that in Comparative Example 1, in which no insulating filler having a particle diameter of 0.02 to 0.143% of the particle diameter of the conductive particles was blended, the difference in number density of the conductive particles could not be reduced. That is, it was found that the dispersibility of the conductive particles was not good in Comparative Example 1. It was also found that in Comparative Example 1, short circuits between electrode terminals of electronic components could not be suppressed, and the conductive particle capture rate was not good. In Comparative Example 1, by using conductive particles (raw particles) 12 not coated with silica filler as shown in FIG. 4, a plurality of conductive particles 12 were linked and aggregated in the insulating binder as shown in FIG. 5.
[0137] In Comparative Example 2, in which the amount of insulating filler with a particle diameter of 0.02 to 0.143% of the conductive particle diameter was set to more than 77.3 volume % (more than 77%) relative to the conductive particles, it was found that the difference in the number density of the conductive particles could not be reduced. That is, in Comparative Example 2, the number ratio of insulating filler with a particle diameter of 0.02 to 0.143% of the conductive particle diameter was excessive, so that the dispersibility of the conductive particles was not good. In addition, in Comparative Example 2, it was found that the short circuit between the electrode terminals of the electronic component could not be suppressed, and the conductive particle capture rate was not good. In Comparative Example 2, it was found that the evaluation of the initial resistance value and the resistance value after the reliability test were both not good. In Comparative Example 2, it was found that after mixing the conductive particles and the silica filler, for example as shown in FIG. 6, coated conductive particles 13 in which two conductive particles are coated with the silica filler were partially formed.
[0138] In Comparative Example 3, in which the amount of insulating filler with a particle diameter of 0.02 to 0.143% of the conductive particle diameter was set to 0.77 volume % (less than 0.78 volume %), it was found that the difference in number density of the conductive particles could not be reduced. That is, in Comparative Example 3, it was found that the dispersibility of the conductive particles was not good because the number ratio of the insulating filler with a particle diameter of 0.02 to 0.143% of the conductive particle diameter was insufficient. In addition, it was found that in Comparative Example 3, short circuits between electrode terminals of electronic components could not be suppressed, and the conductive particle capture rate was not good. [Explanation of symbols]
[0139] REFERENCE SIGNS LIST 1 Connection structure, 2 Anisotropic conductive film, 3 Conductive particle, 4 First terminal row, 5 First electronic component, 6 Second terminal row, 7 Second electronic component, 10 First coated conductive particle, 11 Second coated conductive particle, 12 Conductive particle, 13 Coated conductive particle, 20 Partially coated particle, 21 Large particle, 22 Coated portion, 23 Exposed portion
Claims
1. The coating material comprises coated large particles in which the surfaces of large particles are coated with a small particle size filler, a small particle size filler, and an insulating binder, The coated large particles are dispersed, The large particles have a number average particle size of 2 μm or more and 20 μm or less, the number average particle size of the small particle size filler is 0.02% or more and 0.143% or less of the number average particle size of the large particle, and is 10 nm or more; The resin composition, wherein the amount of the small particle size filler relative to the large particle size filler is 11.6 volume % to 38.7 volume %.
2. 2. The resin composition according to claim 1, wherein said large particles are conductive particles.
3. 3. The resin composition according to claim 1, wherein the small particle size filler is a silica filler.
4. The resin composition according to any one of claims 1 to 3, wherein the large particles have a number average particle diameter of 10 µm or less.
5. The resin composition according to any one of claims 1 to 4, wherein the number average particle diameters of the large particle and the small particle filler are calculated from an image.
6. A step (A) of obtaining first coated particles in which the large particles are coated with the small particle size filler by stirring large particles having a number average particle size of 2 μm or more and 20 μm or less and a small particle size filler having a number average particle size of 0.02% or more and 0.143% or less of the number average particle size of the large particles and 10 nm or more; and (B) a step of stirring the mixture of the first coated particles and the small particle size filler obtained in the step (A) with an insulating binder to obtain a resin composition in which second coated particles, which are the large particle surfaces coated with the small particle size filler, are dispersed in the insulating binder; In the step (A), the large diameter particles and the small particle diameter filler are blended together such that the amount of the small particle diameter filler relative to the large diameter particles is 11.6 vol % to 38.7 vol %; In the step (B), the amount of the small particle diameter filler relative to the large particle diameter filler is 11.6 vol % to 38.7 vol %.
7. The method for producing a resin composition according to claim 6, wherein the number average particle sizes of the large particle and the small particle filler are calculated from an image.
8. An adhesive comprising the resin composition according to any one of claims 1 to 5.
9. An adhesive film comprising the adhesive according to claim 8.
10. The number density of the large particles in the entire adhesive film (pieces / mm 2 ) and the number density (pieces / mm) of the large-diameter particles in a 0.2 mm × 0.2 mm area arbitrarily extracted from the adhesive film. 2 10. The adhesive film according to claim 9, wherein the difference between the thickness and the thickness of the adhesive film is 10% or less.
11. 6. An anisotropic conductive adhesive comprising the resin composition according to claim 1, wherein the large particles are conductive particles.
12. An anisotropic conductive film comprising the anisotropic conductive adhesive according to claim 11.
13. A structure in which a first member and a second member are connected via the adhesive according to claim 8 or the adhesive film according to claim 9.
14. A connection structure in which a first electronic component and a second electronic component are anisotropically connected via the anisotropic conductive adhesive according to claim 11 or the anisotropic conductive film according to claim 12.
15. A method for manufacturing a structure, comprising connecting a first member and a second member via the adhesive according to claim 8 or the adhesive film according to claim 9.
16. A method for manufacturing a connection structure in which a first electronic component and a second electronic component are anisotropically connected via the anisotropic conductive adhesive according to claim 11 or the anisotropic conductive film according to claim 12.
17. The conductive particles include coated conductive particles in which the surfaces of the conductive particles are coated with an insulating filler, an insulating filler, and an insulating binder. the coated conductive particles are dispersed in the insulating binder, The number average particle size of the conductive particles is 7 μm or more and 20 μm or less, the number average particle diameter of the insulating filler is 0.02 to 0.143% of the number average particle diameter of the conductive particles and is 10 nm or more; An anisotropic conductive adhesive, wherein the amount of the insulating filler relative to the conductive particles is 11.6 vol. % to 38.7 vol. %.
18. 18. The anisotropic conductive adhesive of claim 17, wherein the insulating filler is a silica filler.
19. 19. The anisotropic conductive adhesive according to claim 17 or 18, wherein the conductive particles have a number average particle size of 10 μm or less.
20. The anisotropic conductive adhesive according to any one of claims 17 to 19, wherein the number average particle diameter of the conductive particles and the insulating filler is calculated from an image.
21. An anisotropic conductive film comprising the anisotropic conductive adhesive according to any one of claims 17 to 20.
22. The number density of the coated conductive particles in the entire anisotropic conductive film (particles / mm 2 ) and the number density (pieces / mm ) of the coated conductive particles in a 0.2 mm × 0.2 mm area arbitrarily extracted from the anisotropic conductive film. 2 22. The anisotropic conductive film according to claim 21, wherein the difference between the thickness and the thickness of the anisotropic conductive film is 10% or less.
23. A step (A) of obtaining first coated conductive particles in which the conductive particles are coated with the insulating filler by stirring conductive particles having a number average particle diameter of 7 μm or more and 20 μm or less and an insulating filler having a number average particle diameter of 0.02 to 0.143% of the number average particle diameter of the conductive particles and 10 nm or more; and (B) agitating the mixture of the first coated conductive particles and the insulating filler obtained in the step (A) with an insulating binder to obtain an anisotropic conductive adhesive in which second coated conductive particles, the surfaces of which are coated with the insulating filler, are dispersed in the insulating binder; In the step (A), the conductive particles and the insulating filler are mixed together so that the amount of the insulating filler relative to the conductive particles is 11.6 vol.% to 38.7 vol.%; A method for producing an anisotropic conductive adhesive, wherein in the step (B), the amount of the insulating filler relative to the conductive particles is 11.6 volume % to 38.7 volume %.
24. The method for producing an anisotropic conductive adhesive according to claim 23 , wherein the number average particle diameters of the conductive particles and the insulating filler are calculated from the image.
25. A connection structure in which a first electronic component and a second electronic component are anisotropically connected via an anisotropic conductive adhesive described in any one of claims 17 to 20, or an anisotropic conductive film described in claim 21 or 22.
26. The connection structure according to claim 25 , wherein the first electronic component or the second electronic component is a ceramic substrate.
27. A method for manufacturing a connection structure that anisotropically connects a first electronic component and a second electronic component via an anisotropic conductive adhesive described in any one of claims 17 to 20, or an anisotropic conductive film described in claim 21 or 22.
Citation Information
Patent Citations
Production of adhesive for connecting circuit
JP1999148063A
Composition containing conductive particles in which surface-modified nanoparticles are covalently bonded, and method for producing the same
JP2013511813A
Conductive film and connection structure
JP2014241281A
Coated conductive powder, production method for coated conductive powder, and conductive adhesive containing coated conductive powder, and adhesive structure
JP2015133301A
Method for producing resin composition
JP2015134887A